The impact of CSR disclosure on corporate financial performance in Chinese cosmetic industry - Pan, Qichen (2018)
Corporate social responsibility (CSR) has been an important corporate duty in many countries. The disclosure of socially responsible activities is receiving more and more attention from companies. And there are some differences between China and other developed and developing countries. The CSR disclosure in China is constantly improving, but there are still many limitations. This paper tends to study the impact of CSR disclosure on corporate financial performance in Chinese cosmetic industry based on stakeholder theory by analyzing the financial information, annual reports and CSR reports of 20 listed cosmetic firms in SSE and SZSE from 2008 to 2017. Quantitative methods are used to measure variables in this paper. The index is established, and the scoring methodology is used. The results of this study can find the relationship between CSR disclosure and financial performance and provide some guidance to future development of disclosure for Chinese cosmetic companies.